To the knowledge of the Near East species of the genus Odocnemis Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) - Nabozhenko, Maxim V.; Háva, Jiří (Zootaxa, 2020)
A brief review of the eight species of the genus Odocnemis Allard, 1876 from the Near East (Cyprus, Syria, Lebanon, Israel, Jordan, Egypt) is given. All species (excluding probably O. intrusicollis from Cyprus) belong to the praelonga species-group. Odocnemis evae sp. n. is described from Lebanon. The new species is similar to O. praelonga Baudi di Selve, 1876 by the presence of a mucron in females and to O. moabitica Sahlberg, 1908 by the presence of teeth and granules on inner side of metatibiae (at least in large specimens). It differs from both species by the shiny body, the presence a tooth on the outer margin of male pro- and mesotrochanters and by the structure of the aedeagus (very narrow apical piece with ball-like apex). Redescriptions, full bibliographic information and key to the species are given. Odocnemis punctata Allard, 1876 is recorded for Israel for the first time.